(untitled) (International Journal of Engineering and Computer Science, 2014)
Diabetes Mellitus, generally called as High Sugar Problem is a metabolic disorder described by chronic hyperglycemia enhancing rapidly. It is a polygenic disease characterized by abnormal high glucose in the blood. Statistics say that 90 to 95 % of the World Diabetics have Type 2 Diabetes. The consequences of diabetes may be macro vascular complication or micro vascular complication. This proposes a new model for prediction of complications developing due to Diabetes Mellitus. This system compares the performance of various soft computing techniques such as Artificial Neural Networks, Support Vector Machine, Particle Swarm Optimization and Genetic Algorithms for prediction of diabetes disease.